Description of Instructor's Creativity for Improving Learning Motivation on Prima Data Computer Training Skills - Vusri Dewi; Irmawita Irmawita (Universitas Negeri Padang, 2019)
This research is motivated by the high level of creativity of instructors in choosing suitable learning methods, and using interesting and non-boring learning media, so that students can be motivated to take part in learning such as: high attendance rates, high level of student involvement in the process learning, the high level of activeness of students in learning is seen from the activeness of students in asking questions and statements. The type of this research is descriptive quantitative research, the population in this study were computer training students totaling 30 people, based on the number of population used in this study are 22 people using Cluster random sampling technique, and data analysis techniques used in this study are percentages. Based on the results of this study the researcher found: (1) the high level of creativity of instructors in choosing learning methods can improve learning motivation according to the students, it can be seen from the ability of the instructor in choosing suitable and varied methods during the learning process (2) the high level of creativity of instructors in using the media learning can improve students' learning motivation, judging from the ability of instructors to use interesting learning media. Keywords:Instructor’s Creativity, Learning Motivation